Diketahui:

Posted on

f(x) = x² + 3x – 2
g(x)= x + 3
h(x)= 2x – 1
Ditanya:
a.(H•G•F)(x)
b.(H•H•H)(x)
c.(G•G•G)(x)​

Diketahui:

Jawab:

a.) (h o g o f) (x) = h(g(f(x)))

                          =2(x^{2} +3x+1)-1                   g(f(x)) = (x^{2} +3x-2)+3

                          = 2x^{2} +6x+2-1                                = x^{2} +3x+1

                          =2x^{2} +6x+1

b.) (h o h o h) (x) = h(h(h(x)))

                           = 2(4x-3)-1                             h(h(x)) = 2(2x-1)-1

                           = 8x-6-1                                            = 4x-2-1

                           = 8x-7                                               = 4x-3

c.) (g o g o g) (x) = g(g(g(x)))

                           = (x+6)+3                         g(g(x)) = (x+3)+3

                           = x+9                                          = x+6

Semoga Membantu 🙂